UAV Formation Control Using Enhanced Behavior Mechanism And Artificial Potential Field - Luke Deng; Jie Yan; Mingyang Zhao; Jianheng Pan; Xiaoting Bu (Utan Kayu Publishins, 2025)
Inspired by formation flight of pigeon flock, this paper proposes a enhanced method of autonomous formation control of multiple Unmanned Aerial Vehicles (UAVs) that can maintain high symmetry based on pigeon flock behavior mechanism. Addressing the instability of formation in the original method, the follow improvements have been made. Firstly, improve leadership of top three UAVs, Secondly, modify artificial potential field strategies for top two followers. Finally, through a series of simulation experiments, it is verified that the UAVs can form the expected formation under the autonomous formation control, and can maintain the formation under the complex motion of leader UAV.